Radio Internet dalam Perspektif Determinisme Teknologi - Aprilani Aprilani (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2011)
The growth of internet radio has brought a significant impact on change management and radio audiences. Marriage analog radio with internet technology into a new media (Internet Radio) is seen as an alternative solution to some problems of analog radio. Instrumentalist views on Technology Determinism gives the assumption that the function of technology is very dominant in shaping society. Philosophy of technology against this assumption, because Technology Determinism can not explain the meaning and implications of technology for humans. Internet radio using technology to facilitate community access, however the implications of its use to produce new problems in the realm of economic, cultural, social and political. Understanding awareness of the use of technology is the essence of the basic form of critical consciousness of society.